Difference In The Lower Blood Pressure Of Primary Hypertension Patients Participating In Prolanis And Non Prolanis In The Cipayung District Health Center - Latifah Fuat, Alviani; Susanti, Fajar; Ifadah, Erlin (Journal of Ageing And Family, 2021)
Changes in human development at this time greatly affect lifestyles it is a cause of an increase in non- communicable diseases (PTM) one of which is hypertension. Hypertension control has been pursued by the government by implementing a chronic disease prevention program (PROLANIS) through collaboration with BPJS. This study aims to determine the difference in blood pressure reduction in primary hypertension patients who follow prolanis and non prolanis in the Cipayung District Health Center. Pre-experimental research design with static group comparison research. The study population was primary hypertension patients who followed prolanis and non prolanis in the Cipayung District Health Center. Samples were taken by purposive sampling and found 40 people. The collected data is tested statistically by T-test. The results of the study of primary hypertension patients who follow Prolanis have better blood pressure. Statistical test results showed there were differences in blood pressure reduction in primary hypertension patients who followed prolanis and non prolanis (p = 0,000, p <0.05). Nurses provide education to primary hypertension patients who have not yet joined the program to participate in the PROLANIS program.Keyword: Hypertension, Blood Pressure, PROLANIS